Optimal Control Approach For HIV-1 Infection in CD4+T Cells with RTI and PI Treatments - R. Heru Tjahjana; Sutimin Sutimin ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2020)
The purpose of this paper is to expose the optimal approach of controlling HIV-1 infection in CD4+T cells with Reverse Transcriptease Inhibitors (RTI) and Protease Inhibitors (PI) treatments. The scope of the paper includes a proposed model of the dynamic system of HIV-1 infection in CD4 cells with RTI and PI as controls and a proposed objective function model that minimizes infected CD4+T Cells, the population of free virus and therapeutic costs. From the dynamics system model and objective function model, we designed an optimal control for HIV-1 infection control. In this paper, we obtained optimal control for RTI and PI therapies. The results of this paper are as follows: by using the optimal control approach, we obtained infectious control strategy that minimizes actively infected CD4+T Cells, the population of free virus and the cost of treatment. In other words, optimal control is a good approach in determining infection control strategies that minimizes the objective function.